Efektivitas Model Pembelajaran Visual Auditory Kinesthetic (VAK) Terhadap Motivasi Belajar IPS Siswa SMP Dewi Sartika - Rahmah, Aulia; Effendi, Ridwan; Muthaqin, Dwi Iman (The Indonesian Journal of Social Studies, 2024)
Education is essential, it is necessary to constantly improve its quality. This research began with the researcher's field practice, students often complained about the lessons presented by the teacher which seemed tough and boring. It affectsatmospheredecreased learning and impact on decreased student motivation. The aim is to hone teacher skills, as well as prove the application of an interactive learning model, namely the Visual Auditory Kinesthetic learning model which has the principle of combining 3 student learning modalities, while providing new experiences directly to students towards student-oriented learning. Using methodquasi experiment. The results of this study show that after carrying out an analysis of the IBM SPSS version 26 test, the results obtained are sig 0.000<0,05 whch proves that there are differences in learning motivation bertween before and after learning in the experimental class using the Visual Auditory Kinesthetic learning model. Futhermore, the sig 0,000<0,05 and it is found that there is a change in learning motivation in conventional learning. It is obtained if each of the experimental class and control class 0,000<0,05 so that there are differenes in student learning motivation in the experimental class than the control class.